Ajaran Martabat Tujuh dalam Naskah Asrar Al-Khafi Karya Syaikh ‘Abd Al-Mutalib - Masmedia Pinem (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
The doctrines of the martabat tujuh (seven stages) exists in every school of Sufism. This paper discusses the doctrines of the martabat tujuh of Shaikh ‘Abd Al-Mu¯ālib in his work Asrār Al-Khafī. In addition to exposing the doctrine, the author discusses the doctrine in the local social, political and religious context, West Sumatera. The author shows that doctrine of martabat tujuh originated in Aceh, and when it was developed in West Sumatera, it was adjusted by its proponents with local cultures